SARS-CoV-2 vaccine responses following CD20-depletion treatment in patients with haematological and rheumatological disease: a West Midlands Research Consortium study. (30th November 2021) - Shields, Adrian M; Venkatachalam, Srinivasan; Shafeek, Salim; Paneesha, Shankara; Ford, Mark; Sheeran, Tom; Kelly, Melanie; Qureshi, Iman; Salhan, Beena; Karim, Farheen; De Silva, Neelakshi; Stones, Jacqueline; et al.
Abstract: B-cell-depleting agents are among the most commonly used drugs to treat haemato-oncological and autoimmune diseases. They rapidly induce a state of peripheral B-cell aplasia with the potential to interfere with nascent vaccine responses, particularly to novel antigens. We have examined the relationship between B-cell reconstitution and SARS-CoV-2 vaccine responses in two cohorts of patients previously exposed to B-cell-depleting agents: a cohort of patients treated for haematological B-cell malignancy and another treated for rheumatological disease. B-cell depletion severely impairs vaccine responsiveness in the first 6 months after administration: SARS-CoV-2 antibody seroprevalence was 42.2% and 33.3% in the haemato-oncological patients and rheumatology patients, respectively and 22.7% in patients vaccinated while actively receiving anti-lymphoma chemotherapy. After the first 6 months, vaccine responsiveness significantly improved during early B-cell reconstitution; however, the kinetics of reconstitution was significantly faster in haemato-oncology patients. The AstraZeneca ChAdOx1 nCoV-19 vaccine and the Pfizer BioNTech 162b vaccine induced equivalent vaccine responses; however, shorter intervals between vaccine doses (<1 m) improved the magnitude of the antibody response in haeamto-oncology patients. In a subgroup of haemato-oncology patients, with historic exposure to B-cell-depleting agents (>36 m previously), vaccine non-responsiveness was independent of peripheral B-cell reconstitution. The findings have important implications for primary vaccination and booster vaccination strategies in individuals clinically vulnerable to SARS-CoV-2. Abstract : B cell depleting drugs including rituximab are commonly used to treat haematological malignancy and autoimmune diseases but may impair the immunological response to vaccination. This study investigates SARS-CoV-2 vaccine responses in individuals with haematological and rheumatological disease with previously exposure to B cell depleting agents. Vaccination within the first 6 months of B cell depletion is associated with significant impairment of vaccine responsiveness; however, rheumatology and haemato-oncological patients display different kinetics of B cell reconstitution corresponding to differential vaccine responsiveness over time. Graphical Abstract: